Learning Citizenship in the AI ​​Era: A Qualitative Study of Perplexity's Use in Shaping Students' Digital Citizenship - Dedy Ari Nugroho; Sulistiani Sulistiani; Tutik Wijayanti; Mariatul Kiptiah (Universitas Nusantara PGRI Kediri, 2025)
This study aims to explore the use of an AI-based platform, Perplexity, in the Basic and Concept of Citizenship course, viewed from the perspective of digital citizenship. As AI technology continues to advance, teaching approaches in the context of citizenship need to be adapted to be more relevant to the dynamics of the digital society today. The research method used is a qualitative approach with interviews and observations conducted with several lecturers and students who have used the Perplexity platform in citizenship education. This study aims to evaluate the impact of AI platform use on students' understanding of citizenship and how this can support the development of critical and participatory digital citizenship. Two main findings from this study are: first, the use of Perplexity allows students to access information faster and more accurately related to citizenship topics, but challenges arise regarding students' ability to filter and analyze the information provided by the platform. Second, while this platform supports students' digital engagement, there is a tendency for students to rely more on instant answers without deeper reflection, which could affect the depth of their understanding of digital citizenship. This study suggests the importance of integrating digital literacy training into the use of AI technology in citizenship education to support the development of a more critical and responsible citizenship